2013
DOI: 10.1021/ic400554g
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Reaction Mechanism on Nitrile Hydration Catalyzed by [Pd(OH2)4]2+: Insights from Theory

Abstract: Density functional theory methodologies combined with continuum and discrete-continuum descriptions of solvent effects were used to investigate the [Pd(OH2)4](2+)-catalyzed acrylonitrile hydration to yield acrylamide. According to our results, the intramolecular hydroxide attack mechanism and the external addition mechanism of a water molecule with rate-determining Gibbs energy barriers in water solution of 27.6 and 28.3 kcal/mol, respectively, are the most favored. The experimental kinetic constants of the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 109 publications
0
11
0
Order By: Relevance
“…It is known that the use of a discrete‐continuum solvation model, that is, explicit solvent molecules plus a polarizable continuum solvent, is crucial to obtain a more realistic description of the chemical processes in solution when hydrogen transfers or 1,2‐additions of solvent molecules to unsaturated bonds are involved 4e,g. 20 In particular, two theoretical studies have confirmed this fact in aqueous solution for nitrile hydration catalyzed by metal complexes containing molybdenum and palladium 4e,g. For these reasons, and as an initial approximation to the problem, in the case of ruthenium, we explored the intra‐ and intermolecular mechanisms (Scheme ) by using a continuum solvent model (in which the reactant water molecule is clearly taken into account for the intermolecular one).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that the use of a discrete‐continuum solvation model, that is, explicit solvent molecules plus a polarizable continuum solvent, is crucial to obtain a more realistic description of the chemical processes in solution when hydrogen transfers or 1,2‐additions of solvent molecules to unsaturated bonds are involved 4e,g. 20 In particular, two theoretical studies have confirmed this fact in aqueous solution for nitrile hydration catalyzed by metal complexes containing molybdenum and palladium 4e,g. For these reasons, and as an initial approximation to the problem, in the case of ruthenium, we explored the intra‐ and intermolecular mechanisms (Scheme ) by using a continuum solvent model (in which the reactant water molecule is clearly taken into account for the intermolecular one).…”
Section: Resultsmentioning
confidence: 99%
“…[3] It is generally assumed that, upon coordination to the metal center,e lectrond ensity on the nitrile carbon atom drastically decreases, which makes it more susceptible to inter-or intramolecular attack by water or the hydroxidea nion (paths 1a nd 2i nF igure1). [4] The presence, in the coordination sphereo f the metal, of auxiliary ligandsa blet oa ctivate the water molecule by hydrogen bonding has also been recognized as ak ey factor to reduce the activation barrier of the hydration process and improvethe reactionrate (path 3i nF igure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although complexes of metals of groups 6 , and 8–11 ,,,,,, have proven to be active for nitrile hydration reactions, more than half of the reported catalysts are ruthenium compounds, ,,− ,,,,,, and the vast majority of them bear specific ligands that enhance the solubility of the complex in water by means of the formation of hydrogen bonds with solvent molecules. ,,,,,,,,, The improvement of catalysts and reaction conditions have mainly been based on empirical data obtained from trial-and-error methods. Kinetic analysis of the reactions, , isolation of the reaction intermediates, ,, and a density functional theory (DFT) study of the catalysis ,, the three legs of the mechanistic investigationhave received scarce attention. As far as we know, mechanistic proposals based on the three legs together have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…With all of this mind, we undertook a theoretical mechanistic study on the hydrolysis of ethyl acetate catalyzed by [Cp 2 Mo(OH)(OH 2 )] + . Previous theoretical investigations on nitrile hydration , catalyzed by [Cp 2 Mo(OH)(OH 2 )] + and [Pd(OH 2 ) 4 ] 2+ and on carbon monoxide oxidation catalyzed by [Cp 2 Mo(OH)(OH 2 )] + have proven to be useful in getting a more profound rationalization of the most relevant experimental results found in the interesting chemistry of molybdocenes toward organic electrophiles in an aqueous medium.…”
Section: Introductionmentioning
confidence: 99%